VIII. NIH TOOLBOX COGNITION BATTERY (CB): COMPOSITE SCORES OF CRYSTALLIZED, FLUID, AND OVERALL COGNITION. Issue 4 (16th August 2013) - Akshoomoff, Natacha; Beaumont, Jennifer L.; Bauer, Patricia J.; Dikmen, Sureyya S.; Gershon, Richard C.; Mungas, Dan; Slotkin, Jerry; Tulsky, David; Weintraub, Sandra; Zelazo, Philip David; Heaton, Robert K.
ABSTRACT The NIH Toolbox Cognition Battery (CB) includes 7 tests covering 6 cognitive abilities. This chapter describes the psychometric characteristics in children ages 3–15 years of a total summary score and composite scores reflecting two major types of cognition: "crystallized" (more dependent upon past learning experiences) and "fluid" (capacity for new learning and information processing in novel situations). Both types of cognition are considered important in everyday functioning, but are thought to be differently affected by brain health status throughout life, from early childhood through older adulthood. All three Toolbox composite scores showed excellent test–retest reliability, robust developmental effects across the childhood age range considered here, and strong correlations with established measures of similar abilities. Additional preliminary evidence of validity includes significant associations between all three Toolbox composite scores and maternal reports of children's health status and school performance.